Parent, provider and vaccinee preferences for HPV vaccination: A systematic review of discrete choice experiments. Issue 46 (27th October 2020) - Lack, Alina; Hiligsmann, Mickael; Bloem, Paul; Tünneßen, Maike; Hutubessy, Raymond
Abstract: Objectives: To systematically review, appraise and evaluate available evidence regarding discrete-choice experiments (DCEs) for the human papilloma virus (HPV) vaccination in order to support policymakers in making reasonable and effective vaccination program implementation decisions. Methods: A systematic literature review was conducted using the databases PubMed and Embase for DCEs in HPV up to May 2019. Extracted data was tabulated and two checklists were used for the quality appraisal of the included studies. All attributes were categorized in outcome, process or costs attributes and the relative importance of attributes was calculated using the range method. Results: Out of 164 identified studies, 12 met the inclusion criteria. Eight were from high income countries (HICs) and four from low and middle-income countries (LMICs). Five studies each examined vaccinee and parent preferences, while only two assessed the providers' preferences. The studies were rather heterogenous in terms of the populations investigated, the attributes included and the methodologic approach. Overall, outcome measures were the most prominent attributes and effectiveness consistently yielded high relative importance scores. But also process factors, such as the age at vaccination, played an important role for decision making. Discrepancies between HICs and LMICs were most prominent for cost attributes. Conclusion: The heterogenous preferences this review elicited highlight the importance of context when making decisions grounded on consumer preferences. Especially the lack of evidence from LMICs, where the burden of cervical cancer is highest, is worrisome. In order to increase uptake, close vaccination gaps and reduce current inequities in (reproductive) healthcare, policy makers need to understand the features that drive individual vaccination decisions and adapt national and clinical guidelines accordingly. Future research therefore needs to focus on LMICs in order to elicit preferences of those most vulnerable populations.